2022
DOI: 10.21203/rs.3.rs-1798592/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Recovery process of vertical perception and activities of daily living in stroke: A retrospective cohort study

Abstract: It is important to clarify the recovery process of the subjective postural vertical (SPV) and activities of daily living (ADL) in stroke to help clinicians determine treatment plans. This study aimed to investigate the characteristics of the longitudinal recovery process of SPV and ADL after stroke. In total, 109 patients with stroke were enrolled in the study. Clinical assessments included the SPV and total functional independence measure (FIM), both initially and after 1 month. The SPV mean and standard devi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Our results showed that sitting balance training improved variability by enhancing verticality cognition and the ability to perform activities of daily living, as supported by longitudinal studies. [4,5] However, the mechanism by which sitting balance training affects sitting pressure has not yet been clarified. On the other hand, recent reviews have revealed that various sensory and higher brain functions contribute to the vertical perception in balance components.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results showed that sitting balance training improved variability by enhancing verticality cognition and the ability to perform activities of daily living, as supported by longitudinal studies. [4,5] However, the mechanism by which sitting balance training affects sitting pressure has not yet been clarified. On the other hand, recent reviews have revealed that various sensory and higher brain functions contribute to the vertical perception in balance components.…”
Section: Introductionmentioning
confidence: 99%
“…[14–16] Lateral truncal-tilt training can be useful for regaining balance against gravity and the adaptation can be substantial. [5,17,18] The mechanisms of trunk proprioception are affected by the participant training requirements to maintain balance after shifting their weight to a target point. It was suggested that forward reaching of the upper extremity was expected to increase the degree of CoG shift and improve sitting balance ability as its effects.…”
Section: Introductionmentioning
confidence: 99%